Identification of Novel Nexilin Splice Variants in Mouse and Human Tissues - Paul Jung; André Fiedelak; Celina Dreeßen; Otmar Huber; Juliane Reiche (Cells)
There is no doubt that the proper development of the heart is important for its correct function, in addition, maturation processes of the heart are crucial as well. The actin-binding protein nexilin seems to take over central roles in the latter processes, as nexilin-deficient mice are phenotypically inconspicuous at birth but die within short time thereafter. Recently, it has been proposed that nexilin plays a role in the formation and function of transverse tubules (T-tubules), which are essential for excitation-contraction coupling in the hearts of mature animals. Although it has long been known that nexilin is subjected to alternative splicing, a molecular characterization of the respective isoforms is not yet available. Here, we describe novel nexilin splice variants and analyze their expression in tissues of mice and humans. Interestingly, nexilin isoforms segregate to myocyte- and epithelial-specific isoforms. Moreover, heart-specific isoforms of nexilin localize differently between atria and ventricles and are also expressed in the endothelial cells of blood vessels. Further, we narrowed down the critical exons in the actin-binding domains 1 and 2 (ABD1/2), and observed different self-interaction properties by recombinant protein interaction studies. Our results emphasize the diverse tissue and subcellular distribution of the individual nexilin isoforms and point to the importance of taking a closer look at the particular nexilin isoforms investigated.